Evaluation of the Successful Implementation of Enterprise Resource Planning Based on SAP Using the DeLone & McLean Model - Sologia, Filia Eunike; Witjaksono, R. Wahjoe; Ramadani, Luthfi (Universitas Pendidikan Ganesha, 2024)
ERP system is an integrated system that is relied on by companies that aim to improve operational efficiency and optimize company resources. PT XYZ, which is currently engaged in IT, has implemented the use of the SAP ERP system. This study aims to evaluate the success of the ERP implementation at PT XYZ through testing the success of information systems using the DeLone & McLean model. The research method used is quantitative research method and data is collected through filling out questionnaires. This research data processing uses the SEM-PLS method through the SmartPLS application. In determining the sample, non-probability sampling techniques were used. There are 6 DeLone & McLean variables used, namely information quality, system quality, service quality, interest in use, user satisfaction, and net benefits. From the results of the analysis of 9 hypotheses, 5 hypotheses were accepted and 4 hypotheses were rejected. From the test results, the ERP implementation at PT XYZ is still not said to be a direct success with DeLone & McLean testing because there are variables that do not affect each other and are related to interest in using the system by users. Improvements in the system quality, service quality and information quality of the ERP system used will support the successful implementation of ERP technology in the company in the future.